Analysis Of The Effect Of Using Technology In Agricultural Cooperatives On Consumer Behavior: Case Study Of The Koperasi Konsumen Tani Sejahtera Bersama Batam (KTSBB) - Mualam Noor (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this research is to measure of Indonesia's GDP, Exchange Rate and Inflation Rate, on Indonesian exports to Australia for 22 years from 20 00 to 202 2. The data used are secondary data obtained from, World Bank, Bank of Indonesia, BPS and Ministry of Trade. This research uses secondary data with time series data used Multiple Linear regression. The results of this research show that Indonesia's GDP, Inflation Rate, has a positive and significant influence on Indonesian exports to Australia, while Exchange Rate has a (Kalaycıoğlu & Keskin, 2019)negative and significant Indonesian export to Australia.